The Use of Tertiary Alkylmagnesium Nucleophiles in Ni-Catalyzed Cross-Coupling Reactions - Joshi-Pangu, Amruta; Biscoe, Mark R. (Synlett, 2012)
Nickel-catalyzed cross-coupling reactions of unactivated tertiary alkyl nucleophiles and aryl bromides have been developed using N-heterocyclic carbene ligands. These processes are reviewed alongside earlier attempts to employ unactivated tertiary alkyl nucleophiles in cross-coupling reactions. Potential mechanisms for the transformations, and future challenges in this field are discussed.
Keywords: nickel; cross-coupling; transition metals; homogeneous catalysis; Grignard reaction